ACTIVITY OF SOME BRAZILIAN ISOLATES OF ENTOMOPATHOGENIC FUNGI AGAINST THE POULTRY RED MITE DERMANYSSUS GALLINAE DE GEER (ACARI: DERMANYSSIDAE) - Kasburg,CR (2016)
ABSTRACT Poultry red mite Dermanyssus gallinae is a cosmopolitan and hematophagous species commonly found in layer houses around the world. Poultry mite infestations may cause anemia, stress, low body weight and egg production, and mortality. Mite control is typically based on chemical products, but they are not effective and leave residues in eggs; therefore, alternative control methods, such as entomopathogenic fungi, need to researched. This study aimed at evaluating, in the laboratory, the activity of Brazilian isolates of entomopathogenic fungi against D. gallinae. The mites were collected from a commercial layer house and were sprayed with conidial suspensions (1 × 108 conidia/mL) of five isolates of Beauveria bassiana and Metarhizium anisopliae. All tested isolates were pathogenic for the red mite, with confirmed mortality ranging from 22.9 to 52.4%. This demonstrate the potential of the tested entomopathogenic fungi isolates for mite control, and reinforces the need for further studies with other isolates, application strategies, and with fungal formulations.